Mutiara Teguh Enterprise / Nor Erdawati Ahmad... [et al.] - Anoar, Annie Azkiah; Zuber Said, Hafizah; Ghazali, Marlina; Ahmad, Norerdawati (2001)
Mutiara Teguh Enterprise is a company that provide sales petrol and mini market in Seberang Perai, Pulau Pinang. They started their business on 1 January 2005. The type of their company is a partnership company.